Prevalência de anticorpos para Toxoplasma gondii (Nicolle e Manceaux, 1909) em ovinos da região sul do Estado do Rio Grande do Sul - Pappen, Felipe Geraldes (2008)
Serum samples from 1840 sheep from Rio Grande do Sul south (area region), Brazil, were tested to verify the prevalence of IgG antibodies against Toxoplasma gondii by Immunofluorescent Antibody Test (IFAT), using sera dilution 1:64 as cut-off value. Four age groups were studied: one year old, two years old, three years old and > four years old sheep. The prevalence rate for T. gondii infection was 20,2% (450/1840) (15,2% < IC < 26,2%) in sheep, with titers ranging from 1:64 to 1:4096. The prevalence rate of sheep farms, that had at least one positive sheep, was 87,4% (83/95) (78,9% < IC < 92,8%). There was association between antibodies seroprevalence to T. gondii and sheep age, once the one year old group s prevalence was 9,7% (95/687) (6,2%<IC95%<15,0%) and > four years old group s was 35,3% (255/681) (27,5%<IC95%<43,8%). Multivariate logistic regression did not reveal any significant seroprevalence association between sex and other risk factors. The univariate analysis showed presence of housed cats (p=0,17) and not carcasses remotion (p=0,20) as variables with some epidemiological importance. Toxoplasma gondii infection occurs in almost every sheep farms and thus, can be responsable for ovine reproductive losses and human health problems in this region.